Ucieczka od psychoanalizy - Eribon, Didier; Śmieja, Wojciech (Śląskie Studia Polonistyczne, 2015)
The author offers a critical judgment of Lacanian psychoanalysis, pointing out its normativizing aspect. He acknowledges the impossibility of reconciliation of psychoanalytic thought with the theory of radical difference, the example of which is queer, which has been postulated by such scholars as Judith Butler, Lee Edelman or Leo Bersani. As Eribon claims, queer theory constitutes a continuation of (antipsychoanalytic) philosophy of Michel Foucault, and it would be theoretically much more inspiring – Eribon further argues – to try to juxtapose Foucault’s thought with Sartre rather than with Freud or Lacan.